Kemampuan pemecahan masalah matematis siswa berkemampuan awal rendah yang diberikan soal dengan teknik faded-example ditinjau dari teori Polya - Tony Sudaryana; Syamsuri Syamsuri; Sukirwan Sukirwan (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
This research uses a descriptive qualitative research method with the aim of describing the characteristics of students' mathematical problem-solving abilities with low prerequisite mathematical abilities, which are given questions by applying the faded-examples technique, in terms of Polya's problem-solving theory. Based on the discussion of the results and research findings that the characteristics of students' mathematical problem solving abilities with low prerequisite mathematical abilities, which are given questions by applying the faded-examples technique, in terms of Polya's problem-solving theory can be categorized into four categories, namely: reflective, strategic, aware, and incapable. Students with the reflective category have been able to do all the problem solving steps of the Polya procedure. Students with the strategic category have been able to do the first three steps of solving the problem of the Polya procedure. Students with the category of aware are only able to do the first step of solving the problem of the Polya procedure. Students with incapable categories have not been able to do all the steps of solving the problem of the Polya procedure.